Kajian Outdoor Learning Process dalam Pembelajaran Biologi - Deva Dewiyana Sari; Dinda Kinanti; Putri Dewi Sartika; Revita Alief Pramesti; Roza Sani Aidah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Learning Outdoor is a way to increase student learning capacity and encourage student motivation to bridge between theory in books and realities in the field. Learning outside the classroom is not just moving lessons out of the classroom, but instead invites students to unite with nature and make observations of objects in the surrounding environment that lead to the realization of student understanding. The method used in this study is the literature study method. The literature is in the form of various scientific articles published both in scientific journals and proceedings (national or international) and from various other sources. Method approach outdoor learning is seen as very effective as a means of knowledge management which means that each student can develop their abilities based on the experience gained while studying in the open. Of course, this type of learning will have a process that uses interaction, creativity, development of soft skill as well as other things that have a good impact on students. Students who carry out the learning process using the outdoor learning method experience a significant increase in learning motivation where the tendency to increase learning motivation is in the highly motivated category. This shows that students' interest in learning increases by using the method outdoor learning which means they prefer outdoor learning which of course interacts directly with the surrounding environment by observing and understanding various aspects whose purpose is to support the learning process.